Studies on Thyroid Hormones and some Biochemical Constituents of Follicular Fluid in Buffalo - Rampure, D.N.; Dalvi, S. H.; Gudewar, J.G.; Malpani, B.L. (Journal of Buffalo Science, 2014)
Present study investigated the levels of some biochemical constituents and thyroid hormones in follicular fluid and serum and compared their concentrations in different size follicles of buffaloes. Buffalo ovaries with unknown reproductive status were collected from abattoir. The follicles visible on its surface were classified based on their diameter as small (<5 mm), medium (5-10 mm) and large (>10 mm) follicles. Twenty four samples from follicles along with blood samples of buffaloes belonging to respective category were collected. The follicular fluid and the serum samples were analyzed for total proteins, albumin, cholesterol, glucose and hormones tri-iodothyronine and thyroxine. The results of the present study revealed that, there was no specific trend observed in the levels of total proteins and albumin according to the size of the follicles but there was significant difference (P<0.01) in the levels of total proteins in follicular fluid and serum. The levels of total cholesterol showed increasing trend as the size of the follicle increases but the variations are not statistically significant. The serum total cholesterol concentration was significantly higher (P< 0.01) than that of follicular fluid. There was increasing trend of glucose concentration in the follicular fluid and also in the serum of respective buffalo with increase in the size of the follicle but the difference was non-significant. The serum glucose concentrations were significantly higher than the levels in the follicular fluid. There was no variation in the serum levels of triiodothyronine between buffalo bearing small and medium sized follicle while, highest serum level was observed in buffalo bearing large sized follicle. The significant (P≤0.01) increase in the levels of T3 in large sized follicle may attribute to the increase in the activity of monodeioniase enzyme. The follicular fluid thyroxine level showed increasing trend with the size of the follicle but the variation was not significant. There was no significant variation in the levels of T4 in serum and follicular fluid in all the groups.